Queered online pandemic relationships mobile expressions of intimacies, care, and emotion work - Labor, Jonalou S.; Alcazaren, Holden Kenneth G. (2021)
Access online through this link: https://www.plarideljournal.org/article/queered-online-pandemic-relationships-mobile-expressions-of-intimacies-care-and-emotion-work
Keywords: COVID-19 pandemic; Instant messaging; Intimacy (Psychology); Gay male relationships